2019
DOI: 10.1002/qj.3698
|View full text |Cite
|
Sign up to set email alerts
|

The effect of westerlies on East African rainfall and the associated role of tropical cyclones and the Madden–Julian Oscillation

Abstract: Variability of rainfall in East Africa has major impacts on lives and livelihoods. From floods to droughts, this variability is important on short daily time‐scales to longer decadal time‐scales, as is apparent from the devastating effects of droughts in East Africa over recent decades. Past studies have highlighted the Congo airmass in enhancing East African rainfall. Our detailed analysis of the feature shows that days with a westerly moisture flow, bringing the Congo airmass, enhance rainfall by up to 100% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(107 citation statements)
references
References 35 publications
10
92
0
Order By: Relevance
“…Also, the high performance of 2019 OND season was enhanced by the occurrence of the early December, 2019 twine tropical cyclones activities enhanced the performance of the 2019 OND rainfall in Zanzibar and Tanzania at large. The study results had been well agreed with reference [28] which noted that days with a westerly moisture flow, bringing the Congo airmass, enhance rainfall by up to 100% above the daily mean, and these days are more likely during phases 3 and 4 of the MJO and when there are one or more tropical cyclones. The presented results had revealed that for the last short rain seasons the regional ICPAC and TMA forecast reports were significant correct based on the fact that what has been forecasted has been highly observed.…”
Section: Societal Impacts Of the 2019 Ond Rainfallsupporting
confidence: 89%
“…Also, the high performance of 2019 OND season was enhanced by the occurrence of the early December, 2019 twine tropical cyclones activities enhanced the performance of the 2019 OND rainfall in Zanzibar and Tanzania at large. The study results had been well agreed with reference [28] which noted that days with a westerly moisture flow, bringing the Congo airmass, enhance rainfall by up to 100% above the daily mean, and these days are more likely during phases 3 and 4 of the MJO and when there are one or more tropical cyclones. The presented results had revealed that for the last short rain seasons the regional ICPAC and TMA forecast reports were significant correct based on the fact that what has been forecasted has been highly observed.…”
Section: Societal Impacts Of the 2019 Ond Rainfallsupporting
confidence: 89%
“…The amplified Saharan change in temperature is linked to the observed deepening of the SHL, also responsible for the partial recovery of the Sahelian drought (Evan et al, 2015). Thus the SHL plays two key roles: affecting monsoon onset/ retreat and the latitudinal progression of the rain band (Dunning et al, 2018; Lavaysse et al, 2009), and as shown here by affecting zonal winds across central Africa, which are important for water vapor transport and East African rainfall (Finney et al, 2019). Further strengthening of the SHL is expected under climate change (Biasutti et al, 2009; Dong & Sutton, 2015), which through the above mechanisms could lead to further drying of the long rains.…”
Section: Discussionmentioning
confidence: 90%
“…Finney et al (2019) recently demonstrated that although the climatological wind is easterly (Figure S1a in the supporting information), days with westerly winds originating from over the Congo basin do occur during the long rains season, and throughout the year. These events import moist air from over the Congo basin, causing convergence within the Lake Victoria basin, thereby leading to enhanced rainfall, with the record breaking 2018 long rains serving as a prime example (Kilavi et al, 2018).…”
Section: Introductionmentioning
confidence: 87%
“…This advisory also predated the beginning of observed flood impacts by over a week and so we do not consider it to have provided adequate warning of the impacts. Figure 7e shows the impacts of heavy rainfall during the 2018 long rains season, which has been evaluated in depth elsewhere (Kilavi et al, 2018;Finney et al, 2019). Widespread flood impacts were seen across the country, beginning on 14 March and extending throughout the month.…”
Section: Did Advisories Precede Significant Impacts Of Heavy Rainfall?mentioning
confidence: 99%